Post-Traumatic Disorder for a Sample of the Recovered from Corona Disease - Khalil Ibrahim, Lect. Dr. Ikthar (Basra studies journal, 2023)
The aim of the research is to measure Post-Traumatic disorder for a sample of people who recovered from Corona disease in Basrah province for the year (2019-2020) and their number (65) recoveries. The results showed: The sample of those recovering people from Covid 19 that was targeted in the research did not suffer from Post-Traumatic disorder. The Counseling field showed the most area in research sample, followed by avoidance and then recovery of traumatic experience. There are no Statistically significant differences on the Post-traumatic disorder scale according to: (gender, housing, disease severity, age, educational attainment, occupation, recovery period).